Assessment of solid waste management of UP Institute of Civil Engineering - Hadji Ebrahim, Alnoor Y.
Solid waste is a huge environmental problem in both global and local scale. Institutional sources such as educational institution accounts for about 12% of the total solid waste of the country. The main purpose of this research is to assess the current solid waste management system of UP Institute of Civil Engineering Main Building. The assessment involved documentation and evaluation of waste handling practices. Waste generation and composition were also determined through Waste Analysis and Characterization Survey (WACS). Perception Survey was also conducted to gauged the perception and behavior of ICE community towards solid waste management. Lastly, a simple cost analysis was done to determine the best practice for ICE Canteen considering perspective of ICE. It was observed that the janitors of ICE practice collection of recyclable wastes and sell by the end of semester, wherein for this semester it was valued at a total of Php 7, 383. The result of WACS shows that the ICE Canteen accounts for almost half or 44% of total solid waste generated in ICE Compound. Waste generation rate per capita for ICE main building and canteen was calculated to be 30.13g/cap/day and 69.89g/cap/day, respectively, while generation rate per area for ICE Canteen has an average value of 35.84g/sq.m/day. Perception survey responses of students and faculty and staff of ICE were separated, wherein 201 students and 15 faculty and staff participated in the survey. The analysis shows that the students always eat at ICE canteen, while the faculty and staff preferred at their respective offices, but there were quite a few that eats at ICE lobby and classrooms. And most of the respondents were neutral about the current SWM implementation in ICE. The simple cost analysis shows that the proposed use of reusable tableware has lowest B/C ratio of 0.92, than the current practice used of disposable tableware, which is 1.07. While the ideal practice has greater B/C value of 5.13 compare to current practice. Therefore, considering the perspective of ICE and having the highest B/C ratio value, the ideal practice is the best alternative and practice for ICE Canteen. But this may vary if we consider the perspective of the concessionaire and include other factors to be considered. Generally, the UP ICE SWM system lack proper implementation and failed to meet some basic components of OVCCA Memo No CGCG 09-63and stipulation of RA 9003.